Adherence to Safe Sleep Recommendations by Families With Higher-order Multiples. (October 2017) - Haas, Madeline C.; Dowling, Donna; Damato, Elizabeth G.
Abstract : Background: More than 95% of higher-order multiples are born preterm and more than 90% are low birth weight, making this group of infants especially vulnerable to sudden infant death syndrome (SIDS). Emerging evidence suggests that families with twins face challenges adhering to the American Academy of Pediatrics (AAP) recommendations to reduce SIDS risks. Adherence to the AAP recommendations in families with higher-order multiples has not been described. Purpose: This study describes SIDS risk reduction infant care practices for higher-order multiples during the first year of life. Methods: Mothers caring for higher-order multiple-birth infants were recruited from an online support group. An online survey was used to assess infant care practices when the infants were first brought home from the hospital as well as at the time of the survey. Results: Ten mothers of triplets and 4 mothers of quadruplets responded. Less than 80% of the mothers practiced "back to sleep" immediately postdischarge. Supine sleep positioning decreased over time, particularly during daytime naps. Only 50% of the infants shared the parents' bedroom and approximately 30% bed-shared with their siblings. Sleep-time pacifier use was low. Implications for Practice: Safe sleep education must include specific questions regarding home sleeping arrangements, encouragement of breast milk feedings, supine positioning, and pacifier use at every sleep for higher-order multiple infants well before discharge in order for parents to plan a safe sleep environment at home. Implications for Research: Prospective studies to identify barriers and facilitators can inform future strategies supporting adherence to safe sleep practices for higher-order multiple infants.